Assessment of environmental impact of telecommunication base transceivers stations in residential areas - Elehinafe, F. B; Ayeni, A.O; Angela, Mamudu (IOP Conference Series: Earth and Environmental Science, 2021)
This paper assessed the environmental impact of a telecommunication base transceiver stations (BTS) located at Cardoso Close, Apapa, Lagos State, Nigeria with the coordinates 6o4392’N, 3o3126’E. The ambient air quality parameters: SO2, NO, CO, CH4 and total suspended particulates (TSP) were measured using the ITX Emission Analyzer at four sampling points within the base station. The concentrations of SO2, NO, CO and TSP atthe base station ranged between 0.3-0.5 ppm, 1.9-2.2 ppm, 5.5-7.5 ppm, 101-110 µg/m3 respectively for 24-hour averaging period. CH4 was not detected at any of the sampling points. A digital Realistic Sound Level Meter was used in measuring the noise level. The measured average noise levels in all the four sampling points at the BTS studied ranged between 83.1-88.7 dB (A). Samples of water were collected from boreholes around the base station and were subjected tophysico-chemical examinations using the ‘standard methods for water and waste water’ 14th edition prepared by American Public Health Association (APHA). The analyses of the water samples showed that all the parameters are within limits. To measure the electromagnetic radiation emitted from the station during the field study, the SPECTRAN HF-4049 RF, an in-situ dosimeter for radio frequency measurement was used. The results obtained showed that, the measured averageradiation levels in all the four sampling points within the BTS studied ranged between 0.051-0.054 µW/m2. All the measured parameters are within safety margins apart from SO2 and NO. SO2 was not traceable to the BTS while NO was only partly connected with the fossil-fuelled electricity generating sets. The parameters of the physico-chemical analysis of the borehole water were significantly below limits.
Sci. 655 012066
Keywords: STEM; Obafemi Awolowo University; Olayemi Odunlami; Olubunmi Abatan; Adewale Folayan; Jacob Sonibare; Telecommunication base; Transceivers; Residential areas; Environmental Impacts